Effect of thread profile on bending strength of pedicle screw - Rosdi, Daud; Kennedy, S. J.; Mas Ayu, Hassan; A., Shah (IOP Publishing, 2021)
Current pedicle screw designs have not achieved strong bending strength due to varying bone density among patients. Osteoporosis further presents complications in screw fixation and instrumentation failure due patients having less dense bones. We conducted this study to investigate the effect of thread profile on the bending strength of pedicle screw. The study also focus on the bending performance comparison between single threaded and dual threaded pedicle screw via finite element method. The finite element analysis (FEA) was apply to investigate the effect of thread design on the bending strength of pedicle screw (dual threaded, double dual threaded and the dual lead dual threaded screw designs) under normal and osteoporotic bone conditions. The FEA results obtained show that the thread profile does influence the bending strength of a pedicle screw in normal and osteoporotic bones. The dual lead dual threaded pedicle screw showed an improvement of 1.88% in its deflection due to bending. While for the osteoporotic condition, the dual lead dual threaded pedicle screw showed an improvement of 32.3% in term of deflection. Thus, this finding have potential in assisting the optimum pedicle screw design in future although further investigation needed to support this finding.